Satire against Hypocrisy in “The Alchemist” - Shoyimqulova Mahzuna Shavkatovna (International Consortium of Education and Culture Research Studies, 2019)
This paper investigates major points of the Satire against Hypocrisy. On this case the Alchemist were learned and discussed. Satire is a genre of literature in which vices, follies, abuses, and shortcomings are held up to ridicule, drawing reader’s or the audience’s attention to a particular or wider issues in society, with the intent of shaming individuals, institutions, governments, or society as a whole into improvement. Instead of giving helpful advises, the satirist focus on what is wrong and make fun of selfish, mean-spirited people, hoping we will see these qualities in ourselves or people around us and change